Continuity of Midwifery Care for Mrs. C with Breast Engorgement at Deby Cyntya Independent Midwifery Practice: A Case Study - Sopi Aribah Bancin; Ribur Sinaga; Marliani Marliani; Kamelia Sinaga; Deby Cyntia (Jurnal Ners, 2026)
Background: Continuity of Care (CoC) is a comprehensive midwifery care model that provides continuous services from pregnancy, childbirth, postpartum, neonatal care, to family planning. Breast engorgement is one of the most common postpartum problems that may interfere with breastfeeding and reduce maternal comfort if not managed appropriately. Objective: This study aimed to describe the implementation of Continuity of Midwifery Care for Mrs. C with breast engorgement at Deby Cyntya Independent Midwifery Practice in 2026. Methods: This study employed a descriptive case study design using the Continuity of Care approach. Midwifery care was provided comprehensively from pregnancy, labor, postpartum, newborn care, to family planning services. Data were collected through interviews, physical examinations, observations, documentation, and review of medical records. Data analysis was conducted descriptively by comparing the findings with current evidence-based midwifery practices. Results: The implementation of Continuity of Midwifery Care was carried out comprehensively according to the standards of midwifery care. During the postpartum period, Mrs. C experienced breast engorgement, which was managed through breastfeeding education, correct breastfeeding techniques, breast care, warm compresses, oxytocin massage, and family support. Following the interventions, the mother's condition improved, breast engorgement decreased, breastfeeding became more effective, and no complications were identified throughout the continuity of care. Conclusion: Comprehensive Continuity of Midwifery Care contributes to the early detection and appropriate management of breast engorgement, promotes successful breastfeeding, and improves maternal and neonatal health outcomes during the postpartum period.